Technology for Arabic Learning as Foreign Language at Elementary School - Ritonga, Ahmad Roisuddin; Ritonga, Apri Wardana; Ritonga, Mahyudin; Desrani, Ayu (Universitas Muhammadiyah Sumatera Barat, 2024)
The implementation of face-to-face learning in the teaching of Arabic language in elementary schools is an effort to restore the quality of online learning. Therefore, this study aims to describe the management of face-to-face learning (FTF) implementation in Arabic language learning and the problems faced in elementary schools. The results showed that (a) the implementation of Arabic FTF in Elementary Schools has been carried out 100 percent with learning designs using